Consumers’ Preference of Ready to Drink Coffee Food Pairing: Check-All-That-Apply (CATA) Approach - Zulfa Nur Hanifa; Dase Hunaefi; Budi Nurtama (Pusat Penelitian dan Pengembangan Perkebunan, 2021)
Coffee products expand at the same rate as consumer needs. Ready-to-drink (RTD) coffee is a ready-to-drink coffee beverage that is convenient to consume. RTD coffee pairs well with a variety of foods, this combination will produce a sensory trait called Food Pairing. The purpose of this study was to determine the sensory attribute characteristics of RTD coffee and its nourishments using CATA method, as well as the sensory attribute intensity change using modified RATA method. The research process was carried out by initial screening of the panelists, followed by Focus Group Discussion (FGD) to determine sensory attribute and sensory testing, which was carried out using the Home Used Test (HUT). Responses were processed using statistical software XLSTAT and generated a food pairing sensory profile of RTD coffee. The results showed that consumers like RTD coffee paired with chocolate wafer. The